Blood, urine and semen Volatile Organic Compound (VOC) pattern analysis for assessing health environmental impact in highly polluted areas in Italy. (1st October 2021) - Longo, Valentina; Forleo, Angiola; Ferramosca, Alessandra; Notari, Tiziana; Pappalardo, Sebastiana; Siciliano, Pietro; Capone, Simonetta; Montano, Luigi
Abstract: Volatile Organic Compound (VOC) analysis is usually applied in pollution assessment by checking for toxic or harmful volatile compounds in air, water and soil samples. In this study, exogenous VOCs and their derivatives, metabolized by cells, were valued into specific body fluids. In particular, the VOC profiles of blood, urine and human semen samples collected from young men living in two high pollution areas in Italy, i.e. Land of Fires and Valley of Sacco River, were fingerprinted. The analysis is based on Headspace Solid Phase MicroExtraction (HS-SPME) followed by Gas Chromatography-Mass Spectrometric detection (GC-MS). The volatile composition of the three body fluids showed that some VOCs are in common between blood, urine and human semen samples, whereas others are present only in a body fluid. Some compounds, as well as also some chemical classes show a higher affinity for a specific body fluid. Statistical analysis allowed to discriminate the two contaminated areas and identify those compounds which significantly contribute to the two areas classification. Some of these compounds are toxic and found prevalently in Valley of Sacco River samples, correspondingly to sperm analysis results for young men living in this zona worse than those living in Land of Fires. Graphical abstract: Image 1 Highlights: VOCs are distributed differently in blood, urine and human semen samples. VOC pattern can discriminate boy living in Land of Fire and in Valley of Sacco River. Presence of toxic substances in human semen is correlated to a worse sperm quality. Human semen showed to be a good biological fluid for pollutant exposure evaluation. Volatilomics by HS-SPME-GC/MS is a powerful approach to pollution biomonitoring. Abstract : Highest concentration of the detected toxic compounds in human semen of Valley of Sacco River men correspond to worse semen quality.